2018
DOI: 10.3390/ijms19030741
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin Stimulates Proliferation and Migration of Myofibroblasts Isolated from Myocardial Infarction Model Rats

Abstract: Myofibroblasts contribute to the healing of infarcted areas after myocardial infarction through proliferation, migration, and production of extracellular matrix (ECM). Expression of endostatin, a cleaved fragment of type XVIII collagen, increases in the heart tissue of an experimental myocardial infarction model. In the present study, we examined the effect of endostatin on the function of myofibroblasts derived from an infarcted area. The myocardial infarction model was created by ligating the left anterior d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…We examined the migration of RASM by a boyden chamber assay [36,43]. Briefly, the polycarbonate membranes with an 8 µm pore size (Costar, Cambridge, MA, USA) were coated by 2% gelatin (FUJIFILM Wako Pure Chemical) in ddH 2 O (37°C, 30 min).…”
Section: Cell Migration Analysis By a Boyden Chamber Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the migration of RASM by a boyden chamber assay [36,43]. Briefly, the polycarbonate membranes with an 8 µm pore size (Costar, Cambridge, MA, USA) were coated by 2% gelatin (FUJIFILM Wako Pure Chemical) in ddH 2 O (37°C, 30 min).…”
Section: Cell Migration Analysis By a Boyden Chamber Assaymentioning
confidence: 99%
“…We examined the proliferation of RASM with a BrdU incorporation assay kit (Exalpha Biologicals, Shirley, MA, USA) as described previously [36,43]. Briefly, RASM (4.0 × 10 3 cells/well) were seeded on a 96-well culture plate and treated for 48 hr with WsEV, SsEV (0.1, 0.3, 1.0 × 10 8 particles/ml) or PBS (Cont).…”
Section: Cell Proliferation Analysis By a Bromodeoxyuridine (Brdu) Inmentioning
confidence: 99%
“…A review paper demonstrated the effect of ERK1/2 on cell migration through its interaction with different proteins (such as Vinexin β and Calpain 2) [53]. In 2018, a report confirmed via pharmacologically inhibiting the ERK1/2 pathway that endostatin can increase myofibroblast migration through activation of the pathway [44]. In this study, we inferred that BSP could induce HT migration through activation of the ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 54%
“…Results are shown in Figure 6E; PD98059 inhibited BSP-induced proliferation of HTs by 47% compared with BSP group and wortmannin inhibited it by 60%, while co-treatment of both inhibitors inhibited BSP-induced proliferation of HTs by 32%. To confirm the pathway based on Figure 5, we selected PD98059 (PD), one of the MEK/ERK1/2 pathway inhibitors, and wortmannin (Wort), a PI3K/Akt pathway inhibitor, for the cell pathway inhibition experiment [42][43][44]. HTs were treated with two different concentrations of PD98059 (10 and 50 µM) and wortmannin (0.5 and 1 µM) for 1 h and stimulated with 100 µg/mL BSP for 24 h. As shown in Figure 6, PD98059 significantly inhibited the MEK/ERK1/2 pathway at 10 µM (p < 0.01) with maximum inhibition at 50 µM ( Figure 6A,B).…”
Section: Ht Proliferation Testmentioning
confidence: 99%
“…A permanent ligation of left anterior descending coronary artery was performed to make myocardial infarction model rats as described previously [27]. The rats were anesthetized with isoflurane [flow rate: 2 l /min, concentration: 5% (induction), 2.5% (maintenance)] through endotracheal tube connected to a vaporizer (respiratory rate: 100 times/min, tidal volume: 5 m l ).…”
Section: Methodsmentioning
confidence: 99%